2023
DOI: 10.1039/d2ra07240h
|View full text |Cite|
|
Sign up to set email alerts
|

CO2 free production of ethylene oxide via liquid phase epoxidation of ethylene using niobium oxide incorporated mesoporous silica material as the catalyst

Abstract: Ethylene Oxide (EO) is an essential raw material used in various consumer products like different glycol derivatives, ethoxylates, and polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…As we have reported 28 that PAA may play a role in the hydrolysis of EO, potentially leading to a reduction in EO selectivity. 9 Thus, epoxidation should take place at feasible lower catalyst incorporation on the support to reduce epoxide ring opening since a higher catalyst/acidity in the catalyst might lead to more breakdown of PAA and increased hydrolysis of the EO ring. 38 Furthermore, it has been well reported that water produced during the process may promote brønsted acid sites by suppressing Lewis acid sites, and these brønsted acid sites may accelerate the hydrolysis of the epoxide ring.…”
Section: Temmentioning
confidence: 99%
See 2 more Smart Citations
“…As we have reported 28 that PAA may play a role in the hydrolysis of EO, potentially leading to a reduction in EO selectivity. 9 Thus, epoxidation should take place at feasible lower catalyst incorporation on the support to reduce epoxide ring opening since a higher catalyst/acidity in the catalyst might lead to more breakdown of PAA and increased hydrolysis of the EO ring. 38 Furthermore, it has been well reported that water produced during the process may promote brønsted acid sites by suppressing Lewis acid sites, and these brønsted acid sites may accelerate the hydrolysis of the epoxide ring.…”
Section: Temmentioning
confidence: 99%
“…6 As a consequence, there is a need for more research efforts to explore alternative heterogeneous epoxidation catalysts. [7][8][9] In this pursuit, prior investigations have focused on catalysts composed of transition metals in higher oxidation states, which are supported on mesoporous silica materials (MSM), particularly MCM-41 and SBA-15. [10][11][12][13][14] It was noted that the alkene substrate underwent catalysis through a redox reaction, enabling the transfer of oxygen from the oxidant to the alkene double bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, significant concerns were raised regarding metal leaching and H 2 O 2 decomposition with W‐KIT‐6 and Nb‐KIT‐6‐based catalysts [18] . In alignment with prior research efforts, we have developed a highly efficient Nb/MSM catalyst for EO production in our previous research, where peracetic acid (PAA) was used as the oxidant instead of H 2 O 2 , resulting in both superior efficiency and the notable benefit of CO 2 ‐free EO production [7a] …”
Section: Introductionmentioning
confidence: 98%
“…η o PAA andη PAA =Initial and final moles of PAA. Turn over frequency (TOF) is defined as moles of CH 3 COOOH converted per atom of Fe per time [7a] …”
Section: Introductionmentioning
confidence: 99%